Manajemen Pembelajaran Pendidikan Kristen Berbasis Imago Dei: Refleksi kejadian 1:26-27 - Eki Yanto Neonisa; Fransiska Ottu (SERVITA DEI : Jurnal Teologi dan Pendidikan Kristen, 2025)
The learning system in many Christian institutions often still adopts a rigid managerial approach that pays little attention to spiritual values and to the identity as the image of God. This study aims to formulate a concept of Christian educational learning management based on the understanding of Imago Dei as reflected in Genesis 1:26-27. This verse emphasizes that humans are created in the image and likeness of God, which has profound implications for educational approaches, particularly in teaching methods and the relationship between teachers and students. The research method used is a qualitative approach with literature studies and theological reflection as the main instruments in analyzing the concept of Imago Dei and its application in learning management. The results of the study indicate that Imago Dei-based learning management emphasizes respect for the dignity of each individual, the development of holistic potential, and mutually constructive relationships between educators and students.